3+16t-2=8t+113-6t

Simple and best practice solution for 3+16t-2=8t+113-6t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3+16t-2=8t+113-6t equation:


Simplifying
3 + 16t + -2 = 8t + 113 + -6t

Reorder the terms:
3 + -2 + 16t = 8t + 113 + -6t

Combine like terms: 3 + -2 = 1
1 + 16t = 8t + 113 + -6t

Reorder the terms:
1 + 16t = 113 + 8t + -6t

Combine like terms: 8t + -6t = 2t
1 + 16t = 113 + 2t

Solving
1 + 16t = 113 + 2t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-2t' to each side of the equation.
1 + 16t + -2t = 113 + 2t + -2t

Combine like terms: 16t + -2t = 14t
1 + 14t = 113 + 2t + -2t

Combine like terms: 2t + -2t = 0
1 + 14t = 113 + 0
1 + 14t = 113

Add '-1' to each side of the equation.
1 + -1 + 14t = 113 + -1

Combine like terms: 1 + -1 = 0
0 + 14t = 113 + -1
14t = 113 + -1

Combine like terms: 113 + -1 = 112
14t = 112

Divide each side by '14'.
t = 8

Simplifying
t = 8

See similar equations:

| y-2+5(y-4)=y+8 | | x+16y=8 | | 24+r+7r-19+9r+12-r-7= | | x^2-a^2+4a-4=0 | | 25x^2-6x-30= | | a*6-1=15 | | t*3+2=11 | | t*3-2=11 | | 9h-25=56 | | 10m-23=48 | | -1x+8=-2 | | 10g+23=113 | | 2x+132=180 | | -6k-11=-29 | | 15x+132=180 | | 0.54+0.32t=3.12t-1.14 | | -5b+3=33 | | 2x+13x=132 | | 9x^2+157x+598=0 | | 3x+3=8x-7 | | ln(x)+2x=0 | | 4x^2-51x+182=0 | | 8x-(7x+7)=2x-34 | | x+(x*2)=4 | | 3(4+2x)=5(x-1) | | 8x(7x+7)=2x-34 | | 0=2x^2-5x-210 | | 34-7=27 | | 8x^2-15x+9=y | | 8x^2-15x+9= | | 4(57)y=y(6-3) | | 48t=28+140 |

Equations solver categories